Good to be bad: Should we be worried by the sharing economy?. (19th November 2019) - Chalmers, Dominic; Matthews, Russell
Abstract: We develop the notion of a legitimacy tipping point to demonstrate how informal economy practices are being utilized by innovative sharing economy ventures to gain a competitive advantage that is subsequently leveraged to reconfigure formal institutional arrangements. Companies who are able to scale rapidly can afford to contravene regulations, provided they have public support. When they reach a certain size, in terms of investment and customer numbers, regulators are forced into a reactive position where novel business models are legitimized. This raises an important question for regulators and entrepreneurs as to whether subverting business regulation is being viewed as a viable source of competitive advantage by scaling firms.